Implementation of Cloud Computing to Improve Data Management Efficiency in the Education Sector - Rizky Wahyu Hadiyana; Yoyo Subagio (Universitas Muhammadiyah Palu, 2025)
Cloud computing has become a strategic solution in improving the efficiency of data management in the education sector, including in Banten Province. This research aims to explore the implementation of cloud computing and its impact on academic data management in educational institutions. Using a qualitative approach with case studies, data were collected through in-depth interviews and observations of institutions that have adopted cloud systems. The results showed that cloud computing accelerates administrative processes, increases flexibility of data access, and reduces administrative workload. In addition, the cloud supports the development of personalized learning and innovation of digital-based education services. However, the study also found significant challenges, such as limited digital literacy of educators and dependence on internet network infrastructure. Organizational support, through visionary leadership and regular training, proved to be a key factor for successful cloud implementation. On the other hand, data security is a major concern, requiring strategies such as multi-factor authentication, data encryption and role-based access control to reduce the risk of data breaches. By properly managing these challenges, cloud computing not only improves efficiency, but also encourages continuous educational innovation. This research recommends the need for synergy between educational institutions, cloud service providers and local governments to strengthen the education digital ecosystem. A secure, adaptive, and innovation-oriented cloud implementation is expected to accelerate the transformation of education in Banten Province towards competitive and inclusive global standards.